Proinflammatory and Immunomodulatory Gene and Protein Expression Patterns in Spinal Cord and Spleen Following Acute and Chronic High Thoracic Injury - Michael FM; Patel SP; Bachstetter AD; Rabchevsky AG (Dove Medical Press, 2023)
Felicia M Michael,1,2 Samir P Patel,1,2 Adam D Bachstetter,2,3 Alexander G Rabchevsky1,2 1Department of Physiology, University of Kentucky, Lexington, KY, 40536-0509, USA; 2Spinal Cord & Brain Injury Research Center (SCoBIRC); University of Kentucky, Lexington, KY, 40536-0509, USA; 3Department of Neuroscience, University of Kentucky, Lexington, KY, 40536-0509, USACorrespondence: Alexander G Rabchevsky, University of Kentucky, Department of Physiology, Spinal Cord & Brain Injury Research Center (SCoBIRC), B471, Biomedical & Biological Sciences Research Building, 741 South Limestone Street, Lexington, KY, 40536-0509, USA, Tel +1 859-323-0267, Fax +1 859-257-5737, Email agrab@uky.eduIntroduction: In addition to paralysis and loss of sensation, high-level spinal cord injury (SCI) causes sympathetic dysfunction that can lead to autonomic dysreflexia (AD) and chronic immune suppression involving splenic leukopenia. Evidence has shown that treatment with either gabapentin or blockade of TNFα mitigates maladaptive plasticity and the underlying hemodynamic dysfunction, spleen atrophy, and immune dysfunction associated with AD. Because significant improvements long term was noted following treatments only during acute stages of recovery, we sought to systematically examine changes in proinflammatory and immunomodulatory cytokines to ascertain the reason.Methods: Adult female Wistar rats underwent complete T4 spinal transection before euthanasia at systematic intervals from 3 days to 8 weeks after injury. Using qRT-PCR and meso scale discovery (MSD) assays, the gene and protein expression of TNFα and IFNγ in the spleen, upper thoracic (T4-9) and lumbosacral (L5-S6) spinal cords were analyzed.Results: We found that spleen atrophy occurs in a biphasic manner compared to naïve controls, with significant decreases in the spleen mass noted at 3 days and 8 weeks after injury. Splenic TNFα mRNA and protein levels did not change significantly over time, while IFNγ gene expression dipped acutely with trends for increased protein levels at more chronic time points. TNFα protein increased significantly only in thoracic spinal cord segments from 3 to 14 days post-injury. IFNγ mRNA and protein levels remained unelevated in injured spinal cords over time, with trends for increased protein levels at 2 and 8 weeks in the lumbosacral segments.Discussion: Novel temporal-spatial cytokine expression profiles reveal that TNFα protein levels are increased solely in upper thoracic segments after high thoracic SCI, while IFNγ remains unaltered. Splenic leukopenia and latent systemic immunosuppression are not associated with altered TNFα or IFNγ expression in the spleen or spinal cord.Keywords: autonomic dysreflexia, cytokine expression, spleen atrophy, inflammation